DIFFERENTIAL EVOLUTION WITH COMPETITIVE SETTING OF CONTROL PARAMETERS - JOSEF TVRD´IK (TASK Quarterly, 2007)
This paper is focused on the adaptation of control parameters in differential evolution. Competition of various control parameter settings was proposed in order to ensure self-adaptation of parameter values in the search process. Several variants of such algorithm were tested on six functions at four levels of the search-space dimension. The competitive variants of differential evolution have proved to be more reliable and less time-consuming than the standard differential evolution. The competitive variants have also outperformed other tested algorithms in their reliability and convergence rate.